Government debt management and inflation with real and nominal bonds - Lukas Schmid; Vytautas Valaitis; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2022)
In the wake of rising inflation in the aftermath of unprecedented debt financed stimulus packages, we ask: Can governments use real bonds (TIPS) as part of their debt portfolio to commit to stable inflation rates? We propose a novel framework of optimal debt management in the presence of sticky prices with a government that can issue nominal and real non state-contingent bonds. Nominal debt can be inflated away giving ex-ante flexibility, whereas real bonds are cheaper but constitute a real commitment ex-post. Under Full Commitment, the government chooses a leveraged portfolio of nominal liabilities and real assets to use inflation effectively to smooth fiscal policy. When the government cannot commit to future policies, it reduces borrowing costs ex ante using real debt strategically to mitigate incentives for the future government to monetize debt ex-post. Without commitment, the policies are quantitatively consistent with US data, suggesting that such a framework realistically captures the relevant constraints governments face.
Keywords: 330; Optimal Fiscal Policy; Optimal Debt Management; TIPS; Incomplete Markets; Inflation; Inflation Risk Premia; Monetary Policy; Machine Learning; Time Inconsistency